Research of the efficiency of the use of belite sludge for the device of monolithic layers of road clothes by the method of cold recycling - A. A. Lytkin; G. В. Starkov; E. Ya. Wagner (Вестник СибАДИ, 2020)
Introduction. The physical and mechanical properties of belite (nepheline) sludge, a large-tonnage waste of alumina production, are given. The scope of its application is shown in the construction, reconstruction and repair of roads and airfields.Materials and methods. The data of theoretical and laboratory studies on the use of ground nepheline sludge as a binder for strengthening asphalt granulate, including at low temperatures, without antifreeze additives. The optimal dosages of finely ground sludge for strengthening asphalt granulate 10–15℅ have been determined.Results. The results of the experimental studies were confirmed during the production check during the construction of the pilot section of the foundation made of sludge granulometric concrete. The direction of further research is determined.